Rancang Bangun Sistem Mode Persiapan pada Mobil Berbasis Mikrokontroler - Alfan Tamamy; Koesmarijanto Koesmarijanto; Ridho Hendra Yoga Perdana (Jurnal Jaringan Telekomunikasi, 2021)
People want a vehicle that is ready to use without having to wait for long or in the sense that the performance of an activity can run efficiently. With a remote control that can control the vehicle remotely, activities in setup mode will be more efficient. In general, remote control is used in motorized vehicles using Infra-red or Bluetooth communication with communication distance 60meters. So we need LoRa module that has longer beam range. The purpose of research is to design remote control and receiver that can control the vehicle such as opening vehicle door lock,  activating the AC, to the starter mode on the car contact with a wider range of sending and receiving information. The results of research indicate that LoRa module has received signal strength value (RSSI) of -65dBm when LOS (line of sight) at distance 10meters and RSSI of -66dBm at non-LOS (non-line of sight) at the same distance. SNR of 9.25dB when LOS and SNR of 6.0dB when non-LOS at distance 10meters. The research results of sending and receiving remote control data have a maximum distance when non-LOS with obstacles 5mm thick glass and 20 cars is 100 meters with a received signal strength of -112dBm. It can be concluded that for non-LOS connectivity between the LoRa SX1278 has an effectiveness distance at 50meters with an RSSI value of -99dBm and an SNR of 0.25dB, for a LOS condition it has an effectiveness at distance 50meters with RSSI value of -96dBm and SNR of 9dB.